2013
DOI: 10.1111/wre.12063
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and viability of herbicide resistant and susceptible Chenopodium album populations after ensiling, digestion by cattle and manure storage

Abstract: Chenopodium album became a problem weed in sugar beet production, due to resistance to metamitron, a key herbicide in this crop. Dispersal of the seeds from resistant biotypes may occur due to spread by wind, animals, agricultural machinery or manure. This study examined the effect of ensiling, digestion by cattle and storage in slurry and farmyard manure on the germination and viability of the seeds of one susceptible and three resistant C. album populations. After 4 weeks in a maize silo, seed viability of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Higher dormancy could increase survival in silage since most weeds present nondeep physiological dormancy in which structures that protect the embryo play a role in preventing germination (Baskin and Baskin 1998). However, Aper et al (2014) have shown that the viability of seeds from both herbicide resistant and susceptible common lambsquarters does not exceed 5% after four months in corn silage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher dormancy could increase survival in silage since most weeds present nondeep physiological dormancy in which structures that protect the embryo play a role in preventing germination (Baskin and Baskin 1998). However, Aper et al (2014) have shown that the viability of seeds from both herbicide resistant and susceptible common lambsquarters does not exceed 5% after four months in corn silage.…”
Section: Resultsmentioning
confidence: 99%
“…Blackshaw and Rode (1991) demonstrated that a two month storage in barley (Hordeum vulgare L.) silage reduced weed seed viability substantially more than rumen digestion and that in fact adding rumen digestion to silage fermentation did not further reduce the viability of the 12 species tested except wild buckwheat (Polygonum convolvulus L.). Aper et al (2014) also demonstrated that a single month of storage in corn (Zea mays L.) drastically reduced the viability of common lambsquarters (Chenopodium album L.) seeds. Westerman et al (2012) demonstrated that weed seeds of twelve common species stored for 46 d in experimental jars filled with corn had a maximum of 1% viability, except velvetleaf (Abutilon theophrasti Medik) (32% viability).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is to be noted here that seeds containing 2027Cys/Cys ACCase showed an obvious higher vigor after 16 d in the incubator at 40 °C and 100% RH in accelerated ageing experiment, but no difference in P 50 compared with seeds containing wild-type ACCase. A previous study has also showed no difference in P 50 between three resistant and one susceptible Chenopodium album population, but resistant and susceptible C. album used in this study shared several different genetic backgrounds and evolutionary histories, and this may make the conclusion less accurate (Aper et al, 2014).…”
Section: Fitness Cost Depends On the Mutant Accase Allelementioning
confidence: 53%
“…Where y is the viability of the seeds, x is the incubation time, C is the lower limit, D is the maximum germination (i.e. the initial viability) and b indicates the slope around P 50 (Seefeldt et al, 1995;Aper et al, 2014). Seed germination of six derived subpopulation was > 90% when incubation time was shorter than 4 d. Seed viability decreased strongly after 4 d in the incubator, and a very low germination was found after 16 d incubation (2.3% ~ 18.7%) (Figure 5).…”
Section: A Four-parameter Logistic Model Y = C + (D − C)/[1 + (X/ P 50 )mentioning
confidence: 99%